The centralization of the public elementary school in Peru and its early consequences, 1905-1921 - Espinoza, G. Antonio (2020)
In 1905, the Second Civilismo centralized the administration and financing of public elementary schools, as well as the appointment and supervision of teachers. The ideological factors that motivated José Pardo’s regime to take such action included nationalism and positivism, while one of its political motivations was to consolidate its power within Civilismo and over local powerholders. Among the circumstances that favored centralization were the availability of fiscal resources, and the support from some teachers. The consequences of the measure included an increase in the number of schools, growing enrollment, a growing number of teachers (especially women teachers), , the intensification of pedagogical renewal, and the consolidation of a new schoolteachers’ culture.